The Effect of Phytic Acid, Zinc and Soybean Extract on The Growth and Aflatoxin B1 Production by Aspergillus flavus - Sardjono Sardjono (agriTECH, 2010)
It has been reported that aflatoxin contamination in soybean was relatively low, but it was not guaranteed that soybean products is free from aflatoxin contamination. Naturally, soybean containing phytic acid and it bound zinc and protein. Zinc (Zn) is an important mineral for aflatoxin biosynthesis. Previous research indicated that some soybean products such as kecap was contaminated by aflatoxin. It might be Aspergillus flavus involved during kecap fermentation and it produced phytase for phytic acid degradation. Zinc will be released and available for aflatoxin biosynthesis. The aim of this research was to evaluate the effect of phytic acid, Zn and soybean extract on the growth and aflatoxin B1 (AFB1) production by Aspergillus flavus. Five kind of medium were used in the experiment, Glucose Ammonium Nitrate (GAN) medium, a special medium for aflatoxin production, GAN without Zn, GAN supplemented with phytic acid, GAN supplemented with soybean extract instead of glucose and soybean extract supplemented with phytic acid. Two and a half milliliter of spore suspension 07spores/ml) was inoculated into 250 ml of each medium in 1 liter flask. Incubation was done in shaker incubator at room temperature. The growth of mold and AFB production were analyed on 3 and 6 days incubation time. The result indicated that phytic acid lowering the growth of mold in the early 3 days, but not at all after 6 days incubation. It seems that phytic acid delays the aflatoxin production. Lack of Zn in the medium brought about the lowering of aflatoxin production. Even glucose concentration in soybean extract medium was lower than in GAN medium, the growth of the mold was not inhibited but lower on glucose affect on decreasing of AFB1 production.